Meeting the Needs of Data Management Training: The Federation of Earth Science Information Partners (ESIP) Data Management for Scientists Short Course. - Chung-Yi Hou (Issues in Science and Technology Librarianship, 2015)
With the proliferation of digital technologies, scientists are exploring various methods for the integration of data to produce scientific discoveries. To maximize the potential of data for science advancement, proper stewardship must be provided to ensure data integrity and usability both for the short- and the long-term. In order to assist scientists and their library and information partners to gain familiarity, skills, and knowledge of data management, the Federation of Earth Science Information Partners (ESIP) has developed the Data Management for Scientists Short Course. The Short Course provides training on a range of data management topics, including metadata, file formats, and interoperable content. This paper provides an overview of the background and motivation for data management, followed by an introduction to the Short Course. The discussion on the Short Course' features demonstrates the advantages of learning the fundamentals of data management through the Short Course. The paper concludes by emphasizing the importance of familiarity with data management practices for both researchers and their library and information partners. [ABSTRACT FROM AUTHOR]